(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
This article examines the historical significance of the Qin (221–206 BCE) and Han (206 BCE–220 CE) dynasties in the context of Chinese civilization. The Qin Dynasty, though short-lived, played a crucial role in unifying China, centralizing power, and laying the foundations for imperial rule. The Han Dynasty, which followed, expanded the empire, established a strong bureaucratic system, and made significant advancements in technology, culture, and trade. These two dynasties not only shaped the political and social structure of ancient China but also had a profound influence on East Asia and the world.